Designing Interactive Digital Media for Arabic Reading Learning: Development and Validation of Ayo Qira - Wihada Ahliya Shakira; Zukhaira Zukhaira (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
The limited availability of interactive digital learning media and students’ difficulties in comprehending Arabic reading texts remain significant challenges in developing Arabic reading skills (mahārah qirā’ah) in Islamic secondary education. This study aimed to design and validate Ayo Qira (Ayo Qirā’ah Asyik), a Genially-based interactive learning medium developed to support independent and engaging Arabic reading instruction. The study employed a Research and Development (R&D) approach using the Hannafin and Peck model, encompassing needs assessment, design, development, and implementation stages. Data were collected through student needs analysis questionnaires involving 50 eleventh-grade students, semi-structured interviews with Arabic language teachers, and expert validation instruments. The validation results indicated a mean score of 4.71 out of 5, categorizing the media as highly feasible for instructional use. The developed media integrates reading materials, vocabulary enrichment, comprehension activities, and game-based formative assessments within a flexible digital learning environment. The findings demonstrate that Ayo Qira provides an innovative learning resource that supports students’ engagement with Arabic texts while facilitating autonomous learning. This study contributes to the growing body of research on technology-enhanced Arabic language learning by offering a validated digital media model that can be adapted for reading instruction in similar educational contexts.